AB0325 Comparison of Activity Score DAS28-ESR and DAS28 -CRP in Patients with Rheumatoid Arthritis. (10th June 2014) - Ben Slama, I.; Allali, F.; El Kabbaj, S.; Lakhdar, T.; Medrare, L.; Ngeuleu, A.; Rkain, H.; Hajjaj-Hassouni, N.
Abstract : Objectives: To compare the disease activity score (DAS)28- ESR versus DAS28 -CRP, and to determine the factors that might influence their difference. Methods: Patients with RA were included in a cross-sectional study. We have collected the demographic characteristics and the characteristics of the RA: duration of evolution, morning stiffness in minutes, functional impact of the disease assessed by the HAQ (Health Assessment Questionnaire), and current corticosteroid dose. The disease activity was assessed by the DAS28-ESR and DAS28-CRP. A simple correlation between DAS28-ESR and DAS28-CRP was performed. We considered a difference between DAS28-ESR and DAS28-CRP as significant when it is greater than or equal to 0.6 [1]. Factors influencing this difference were tested by univariate then multivariate logistic regression. Results: 103 patients were included with a female predominance (87.4%). Mean age was 49.7±11.4 years. Median disease duration was 8 years [3-14]. There was a strong positive correlation between the two indexes of 0.91 (p<0.001), although the DAS28-ESR value obtained was higher than that of DAS28-CRP at approximately 90% of the visits (n=93). Significantly, the difference between both indexes was higher than 0.6 in 42.7% of the visits studied (n=44). In univariate analysis the difference between DAS28-ESR and DAS28 -CRP was associated with a significant pain intensity (OR =1.069, 95% CI [1045-1094], p<0.0001), a prolonged morning stiffness (OR =1.022, 95% CI [1011-1034], p<0.0001), a significant functional impairment (OR =5.430, 95% CI [2738-10767], p<0.0001), a high dose of steroids (OR =1.276, 95% CI [1026-10467], p=0.029). The multivariate analysis showed that factors remained significantly associated with this difference was the intensity of severe pain (OR =1.052, 95% CI [1023-1082], p<0.0001) and HAQ (OR =2.502, 95% CI [1106-5656], p=0.028). Conclusions: Our study shows a strong positive correlation between the DAS28-ESR and DAS28 -CRP. But DAS VS 28 would be higher than the DAS28 CRP in patients with high pain intensity and significant functional impairment. References: Are the C-reactive protein values and erythrocyte sedimentation rate equivalent when estimating the 28-joint disease activity score in rheumatoid arthritis? Clin Exp Rheumatol. 2008 Sep-Oct;26(5):769-75. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5807